2017
DOI: 10.14202/vetworld.2017.149-155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of lecithin and carnitine on growth performance and nutrient digestibility in pigs fed high-fat diet

Abstract: Aim:To study the effect of dietary supplementation of lecithin and carnitine on growth performance and nutrient digestibility in pigs fed high-fat diet.Materials and Methods:A total of 30 weaned female large white Yorkshire piglets of 2 months of age were selected and randomly divided into three groups allotted to three dietary treatments, T1 - Control ration as per the National Research Council nutrient requirement, T2 - Control ration plus 5% fat, and T3 - T2 plus 0.5% lecithin plus 150 mg/kg carnitine. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…However, Kim et al (2008) observed no differences in digestibility of DM, energy, protein and ether extract with supplementation of 2.5% and 5% of lecithin in finishing pigs. Saseendran et al (2017) reported that in the digestibility coefficient of nutrients and minerals of piglets, no significant change was observed with 0.5% lecithin diet. It was reported that nutrient digestibility could be affected by fat types included in the diets (Mitchaothai et al 2008); therefore, the inconsistency among studies may be related to the type of lecithin and fat and the age of animals.…”
Section: Growth Performance and Nutrient Digestibilitymentioning
confidence: 97%
“…However, Kim et al (2008) observed no differences in digestibility of DM, energy, protein and ether extract with supplementation of 2.5% and 5% of lecithin in finishing pigs. Saseendran et al (2017) reported that in the digestibility coefficient of nutrients and minerals of piglets, no significant change was observed with 0.5% lecithin diet. It was reported that nutrient digestibility could be affected by fat types included in the diets (Mitchaothai et al 2008); therefore, the inconsistency among studies may be related to the type of lecithin and fat and the age of animals.…”
Section: Growth Performance and Nutrient Digestibilitymentioning
confidence: 97%
“…Several studies have shown that dietary emulsifier supplementation significantly increased body weight, average daily gain, average daily feed intake and reduced feed weight of broiler [22][23][24][25]. Furthermore, the addition of lecithin to the broiler diet has been shown to significantly improves the digestibility of feed fat, leading to increased weight gain of broilers and improving feed conversion rate [26][27][28]. The results of this experiment align with these findings, as dietary emulsifier supplementation significantly increased and promoted the ADG of yellowfeathered broilers aged 43 to 63 days, consistent with the results of the aforementioned studies.…”
Section: Effect Of Emulsifier On Growth Performance Of Yellowfeathere...mentioning
confidence: 99%